Analysis of the SAW Model in the Selection of Majors at ISB Atma Luhur - Fitriyani, Fitriyani; Irawan, Devi; Andrika, Yuyi; Adiwinoto, Bambang (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2023)
The department is part of the faculty, and is the focus of the field of study chosen by students. The choice of majors is very important to think about beforehand because it will have an impact on the results of these graduates and the job prospects sought later. There are many things that can be considered by high school graduates in choosing a major because if you choose rashly, you will be at risk of failing along the way. For this reason, research was carried out with an emphasis on the criteria for selecting majors at ISB Atma Luhur. The method used in this study is SAW (Simple Additive Weighting) which is a weighted sum method that is weighting criteria and alternative attributes so that normalization can be carried out and calculation of preference values is carried out and the highest and lowest rankings are obtained which are used as decision recommendations. Respondent data was taken based on the sample, namely through a non-probability sampling technique, namely in this study the respondent could only provide one opportunity to be sampled from the population so that one respondent could not be sampled twice. Respondents who were sampled were 100 people who were taken from high school graduates. The criteria presented include department accreditation, number of professionally certified lecturers, study program scholarships, and facilities. Determination of criteria based on the results of interviews with respondents and the results are taken based on the criteria with the most choices. The results of the study are alternative Information Systems with a weight or value obtained from the SAW calculation results, namely 1, Informatics Engineering with a weight of 0.8, while Digital Business is 0.6. From the results of these calculations, it can be concluded that the department that gets the highest score, namely the Information Systems major, can also be used as a recommendation as a major to be chosen by students.